2015
DOI: 10.1007/s00784-015-1477-5
|View full text |Cite
|
Sign up to set email alerts
|

Carious deciduous teeth are a potential source for dental pulp stem cells

Abstract: Decayed deciduous teeth have been usually discarded once the pulp tissue could be damaged and the activity of stem cells compromised. These findings show that stem cells from carious deciduous teeth can be applicable source for cell-based therapies in tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 26 publications
3
42
0
1
Order By: Relevance
“…Werle et al . () reported a successful DPSC isolation rate of 70% for carious primary teeth and 100% for healthy primary teeth. These authors did not find any contamination of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Werle et al . () reported a successful DPSC isolation rate of 70% for carious primary teeth and 100% for healthy primary teeth. These authors did not find any contamination of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hDPCs can differentiate to a matrix mineralization phenotype (Gronthos et al, 2000, 2002; d'Aquino et al, 2007; El-Gendy, 2010), while controversial data have been published regarding cDPCs isolated from permanent (Alongi et al, 2010; Wang et al, 2010; Pereira et al, 2012; Ma et al, 2014; Yazid et al, 2014) or deciduous (Yu et al, 2014; Werle et al, 2015) teeth affected by deep caries. Our data clearly show that cDPCs isolated from shallow carious lesions can differentiate to this phenotype and form a mineralized matrix (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…compared the enzyme digestion and outgrowth methods and found that cells isolated by enzyme digestion had a higher proliferation rate than those isolated by the other methods. In this study, the enzymatic digestion method used in the studies of Yu, et al [13], Bernardi, et al [14], Werle, et al [2], and their colleagues, was employed.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the ability of the cells to differentiate, 10 4 cells/cm 2 (at the fifth passage) were plated in 12-well plates and cultivated in appropriate media osteogenic, adipogenic and chondrogenic differentiation for 2 to 4 weeks after reaching at least 70% confluence [2]. For each experiment, a negative control was used consisting of the same cells maintained in conventional culture medium.…”
Section: Cell Differentiation In Vitromentioning
confidence: 99%